“Before, there was no such thing”: Contemporary Czech Prose and Topics of Migration - Derdowska, Joanna (Porównania, 2022)
While in the contemporary Czech public discourse, the ethos of emigration from the Czechoslovak times remains alive and supported by cultural production. The Czech Republic is becoming an immigrant country and there is a clearly discernible space for literature written by and about migrants in its literary field. Since authors whose biographies would allow this literature to be written with the license of “authenticity” are scarce, narratives about the migration experience are intermediated, mainly by writers who form the contemporary Czech canon and/or literary mainstream. On the basis of selected texts dealing with this topic, we can point to several strategies of representing the experience of migration (including economic migration) and displacement (the subversive potential of demographic changes, the didactic basis of attempts to create universalizing narratives about exile, attempts to create a Czech refugee subject), as well as the tropes through which this literature potentially opens up to the discourse of postmigration.